Research on joint simulation technology of fire dynamics and servo control of self-propelled antiaircraft gun during moving. (March 2020) - Gao, X K; Gu, B; Zhou, C J; Liu, J
Abstract: Taking self-propelled anti-aircraft gun as the research object, this paper presents a joint simulation method of shooting dynamics and servo control during the course of self-propelled anti-aircraft gun. Aiming at the matching between structural parameters and servo control parameters of self-propelled anti-aircraft gun, an evaluation and optimization design method is proposed. The platform of the joint simulation system of dynamics and servo control is mainly composed of road-body-turret dynamics model, fire control module, elevation control compensation module, azimuth control compensation module and motor module. The control compensation module realizes the control strategy by PID (Proportional-Integral-Differential) control of position and speed loop. The motor module achieves the system control torque output through the current loop and the motor. These modules constitute the joint simulation design model of dynamics and servo control. By comparing the output of the simulation system with the actual firing test results of self-propelled antiaircraft gun, the effectiveness of the method is verified by the firing line error analysis under different experimental conditions. This method can be used to evaluate the tracking accuracy of the system at the design stage, which is helpful to reduce the development cost and shorten the development period.